Impact of Bt corn expressing Bacillus thuringiensis Berliner insecticidal proteins on the growth and survival of Spodoptera frugiperda larvae in Colombia - Rodríguez Chalarca, Jairo; Valencia, Sandra J; Rivas-Cano, Alejandra; Santos-González, Francisco; Romero, Diana Patricia (Frontiers Media, 2024)
Bioassays were conducted under controlled conditions to determine the response of Spodoptera frugiperda (J. E. Smith) larvae fed with corn materials expressing Bacillus thuringiensis (Bt) insecticidal endotoxins: (1) VT Double Pro ® (VT2P) expressing Cry1A.105-Cry2Ab2 proteins and (2) VT Triple Pro ® (VT3P) expressing Cry1A.105-Cry2Ab2-Cry3Bb1 proteins. The parameters assessed were: (i) mortality rate, and (ii) growth inhibition (GI) with respect to the control. To conduct this study, larvae were collected from commercial non-Bt corn fields, in four agricultural sub-regions in Colombia, between 2018 and 2020. Fifty-two populations were assessed from the field and neonate larvae from each of the populations were used for the bioassays. The study found that mortality rates in the regions for larvae fed with VT2P corn ranged from 95.1 to 100.0%, with a growth inhibition (%GI) higher than 76.0%. Similarly, mortality rate for larvae fed with VT3P corn were between 91.4 and 100.0%, with a %GI above 74.0%. The population collected in Agua Blanca (Espinal, Tolima; Colombia) in 2020, showed the lowest mortality rate of 53.2% and a %GI of 73.5%, with respect to the control. The population that exhibited the lowest %GI was collected in 2018 in Agua Blanca (Espinal, Tolima, Colombia) with a 30.2%, growth inhibition, with respect to the control. In recent years, the use of plant tissue to monitor susceptibility to fall armyworm has proven to be useful in the resistance management program for corn in Colombia determining that the FAW populations are still susceptible to Bt proteins contained in VT2P and VT3P.